2018
DOI: 10.1017/s0033291718001101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the proposed ICD-11 PTSD diagnostic criteria

Abstract: This study indicates that significantly fewer individuals would be diagnosed with PTSD using the proposed ICD-11 criteria. Though ICD-11 criteria identify more severe cases, those meeting ICD-10 but not ICD-11 criteria remain in the moderate range of PTSD symptoms. Use of ICD-11 criteria will have critical implications for case identification in clinical practice, national reporting, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 32 publications
1
24
0
4
Order By: Relevance
“…Unfortunately, we do not know to what extent participants experienced intrusive memories in the present, but rather only the reported intensity. At this point, however, items on the CAPS have been largely used and accepted in the approximation of ICD symptom criteria (e.g., Barbano et al, 2018;O'Donnell et al, 2014;Wisco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, we do not know to what extent participants experienced intrusive memories in the present, but rather only the reported intensity. At this point, however, items on the CAPS have been largely used and accepted in the approximation of ICD symptom criteria (e.g., Barbano et al, 2018;O'Donnell et al, 2014;Wisco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also demonstrated that the ICD-11 PTSD criteria identify only a subset of the individuals previously identified as having PTSD by the ICD-10 criteria (Barbano et al, 2018;Gluck et al, 2016;Haravuori, Kiviruusu, Suomalainen, & Marttunen, 2016;Tay et al, 2017), allowing comparisons between participants identified by the ICD-11, the ICD-10, and the ICD-10 only. Previous research has also demonstrated that the ICD-11 PTSD criteria identify only a subset of the individuals previously identified as having PTSD by the ICD-10 criteria (Barbano et al, 2018;Gluck et al, 2016;Haravuori, Kiviruusu, Suomalainen, & Marttunen, 2016;Tay et al, 2017), allowing comparisons between participants identified by the ICD-11, the ICD-10, and the ICD-10 only.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations